Pengembangan Bahan Ajar Berbasis Addie Model: Addie Model-Based Teaching Material Development - Cahyadi, Rahmat Arofah Hari (Halaqa: Islamic Education Journal, 2019)
Instructional material are an important part in determining the quality of learning. The design of the development of instructional material needs to pay attention to the development model to ensure the quality of instructional material in supporting learning effectiveness, because the development of instuctional material is basically a linear process with the learning process. One of the designs for the development of instructional material that is often used is the ADDIE Model through 5 stages; Analysis, Design, Development, Implementation and Evaluation. The ADDIE model is a learning system design model that shows the basic stages of a learning system that is easy to do.